Tauhid Sebagai Dasar Prinsip Pengetahuan Dalam Pandangan Ismail R. al-Faruqi - Habibi, M. Dani (Indonesian Journal of Islamic Theology and Philosophy, 2024)
Abstract;This study explores the concept of Tawhid in the thoughts of Ismail R. al-Faruqi as a basic principle of knowledge in his view. Tauhid, a core concept in Islam which emphasizes the unity and oneness of Allah, is a deep foundation in understanding the universe and human life according to al-Faruqi. In his perspective, the concept of Tawhid is not only theological, but also has significant epistemological implications. This research highlights how al-Faruqi links Tawhid with Islamic epistemology, reinforcing the idea that the unity of knowledge and existence is a reflection of the unity of Allah. The research method used is qualitative (literature review). By expanding the scope of Islamic epistemology through the concept of Tawhid, al-Faruqi offers a solid foundation for understanding the relationship between knowledge, religion and human life in a holistic framework. Through a text and contextual analysis approach, this study outlines al-Faruqi's contribution in bringing a new understanding of the role of Tawhid in building sustainable and comprehensive knowledge principles in contemporary society.Keywords:Ismail R. al-Faruqi; Knowledge; Tauhid. AbstrakKajian ini mengeksplorasi konsep Tauhid dalam pemikiran Ismail R. al-Faruqi sebagai dasar prinsip pengetahuan dalam pandangannya. Tauhid, konsep inti dalam Islam yang menekankan kesatuan dan keesaan Allah, merupakan fondasi yang mendalam dalam memahami alam semesta dan kehidupan manusia menurut al-Faruqi. Dalam perspektifnya, konsep Tauhid tidak hanya bersifat teologis, tetapi juga memiliki implikasi epistemologis yang signifikan. Penelitian ini menyoroti bagaimana al-Faruqi menghubungkan Tauhid dengan epistemologi Islam, memperkuat gagasan bahwa kesatuan ilmu dan keberadaan adalah refleksi dari kesatuan Allah. Metode penelitian yang digunakan adalah kualitatif (Kajian Pustaka). Dengan memperluas cakupan epistemologi Islam melalui konsep Tauhid, al-Faruqi menawarkan landasan yang kokoh untuk memahami relasi antara pengetahuan, agama, dan kehidupan manusia dalam kerangka yang holistik. Melalui pendekatan analisis teks dan kontekstual, kajian ini menguraikan kontribusi al-Faruqi dalam membawa pemahaman baru tentang peran Tauhid dalam membangun prinsip-prinsip pengetahuan yang berkelanjutan dan menyeluruh dalam masyarakat kontemporer.Kata Kunci:   Tauhid, Knowledge, Ismail R. al-Faruqi.